VEHICLE IDENTIFICATION IN PARKING AREAS USING ADAPTIVE BRIGHTNESS THRESHOLDING - Rosyidi, Mohammad; Bismantoko, Sahid; Widodo, Tri (BPPT, 2020)
The problem of parking systems on the street is a classic problem that occurs from year to year, manysolutions are offered in solving the parking problem on the street. The problem is not only related to trafficjams due to in and out of vehicles from the parking spaces but also the parking management issues becomepolemic at this time. A prototype of parking management monitoring system tries to provide solution inmanaging parking by using image processing based smart camera. In a prototype the system test performedon day and night conditions, to anticipate the very contrast difference intensity of pixels during the day or night so as to develop vehicle detection program using adaptive brightness thresholding. The results showthat the program has been running quite well to identify vehicles during day and night timeframe